Production of Several Types of Vegetables in the Composition of the Growing Media Cultivated in a Verticulture - Ramdan Hidayat; Purnomo Edi Sasongko; Nora Augustien (Future Science, 2021)
Mitigation of the risk of decreasing food security in urban areas can be done through the use of yardland through urban agriculture which is currently being carried out by urban communities since staying at home is one of the family's independent food solutions by cultivating short-lived vegetables (3-4 weeks) with a multilevel agricultural cultivation system. or ver-tical. The purpose of this study was to determine the composition of the growing media which resulted in the best production of three types of veg-etable crops cultivated vertically. The research was carried out in the ex-perimental garden of the Faculty of Agriculture, UPN